Pelayanan Sosial Pekerja Sosial Medis di Rumah Sakit Dr. Soetomo Surabaya - M, Musfikirrohman; Rahmawati, Atik (University of Jember, 2016)
Abstract Hospital are institution that deal with public health problem for both medical and non medical. Service in the medical field made by the medical team, whereas the non medical service performed by medical social worker to deal with social problem in patient. Focus this study in research about social service of medical social worker in hospital. The hospital also has a field of non medical service one of which is Dr. Hospital. Soetomo, where the ministry seeking holistic service in both the medical and non medical service.. Dr. Soetomo hospital have a one social worker at the medical paliatif & free Pain. Social workers will serve in and out of the hospital, like a visit in a home to the care of patients. A patient's medical workers from the social services such as a defect an amputation, paralyzed, and young people with the poor condition. Forms of administrative services, such as the motivation, a device to help you, the drugs, for the and education to propose problems.